Comparison of fecal near-infrared with conventional methods to estimate intake and digestibility in sheep - Parra-Forero, Diana (2023)
Introduction. Intake and digestibility are parameters that define the quality of a forage; however, they are difficult and expensive to estimate. Near infrared spectroscopy technology applied to feces (NIRSf) is an alternative to conventional reference methods to estimate dry matter voluntary intake (DMVI) and digestibility (DMD) in sheep. Objective. To compare NIRSf technology with conventional methods for estimation of DMVI and DMD in confinement sheep. Materials and methods. Six bioassays were carried out at the Tibaitata research center, Cundinamarca, Colombia, during 2019 and 2021 with five sheep (LW 58.28±11 kg) to estimate DMVI and DMD by three methods: gravimetry, markers and NIRSf. The animals were fed six diets contrasting in their nutritional value. Forage and feces samples were collected, dried, and ground for subsequent chemical and spectral analysis. Results. The estimation of DMVI and DMD was different (p<0.001) in the six evaluated feeding regimenes, where the DMVIMW ranged from 37.54 to 82.58 g/kg LW0.75, and the DMD ranged from 36.32 to 58.81 %. In the comparison of the estimation of DMVI and DMD by the referent method (gravimetric) with marker and NIRSf methods, shows that the NIRSf method presented a better adjustment compared to the marker method, presenting less root mean square error value (-1.53 and -1.75, respectively), lower mean absolute error (-3.01 and -0.5, respectively), and higher determination coefficient (+0.09 and +0.28, respectively). Conclusion. The estimation of the DMVI and the DMD by means of the NIRSf equations presented a better fit compared to the marker method, however, it is necessary to improve the accuracy of the calibrations using feces samples from animals under different productive contexts.